The sustainable management of tourism development impacts in Sagada, Mountain Province with the aid of Geographical Information Systems - Fresnoza, Eli Paolo R. 1980-
This paper describes how cultural and natural assets of Sagada may be more efficiently and sustainably managed. These assets are the primary reason why toursim in Sagada exists, and ironically, it is the development of this tourism industry that maybhave the potential to damage and destroy these natural and cltural assets. To aid in managing these resources, the capacities of Geographical Information Systems (GIS) alongside the concept of sustainable planning are employed. Beneficial in using GIS is inventory management as well as discovering present and potential impacts of development various natural and cultural resources.
"April 2008."
Vita.
Thesis (M.A. Urban & Regional Planning)--University of the Philippines Diliman.
Keywords: Tourism -- Management -- Philippines -- Sagada (Mountain Province); Ecotourism -- Philippines -- Sagada (Mountain Province); Land use -- Planning -- Philippines -- Sagada (Mountain Province)